Cutaneous abnormalities in rheumatoid arthritis compared with non-inflammatory rheumatic conditions. Issue 10 (13th February 2006) - Douglas, K M J; Ladoyanni, E; Treharne, G J; Hale, E D; Erb, N; Kitas, G D
Abstract : Background: Cutaneous abnormalities are common in rheumatoid arthritis, but exact prevalence estimates are yet to be established. Some abnormalities may be independent and coincidental, whereas others may relate to rheumatoid arthritis or its treatment. Objectives: To determine the exact nature and point prevalence of cutaneous abnormalities in patients with rheumatoid arthritis compared with those in patients with non-inflammatory rheumatic disease. Methods: 349 consecutive outpatients for rheumatology (205 with rheumatoid arthritis and 144 with non-inflammatory rheumatic conditions) were examined for skin and nail signs by a dermatologist. Histories of rheumatology, dermatology, drugs and allergy were noted in detail. Results: Skin abnormalities were reported by more patients with rheumatoid arthritis (61%) than non-inflammatory controls (47%). More patients with rheumatoid arthritis (39%) than controls (10%) attributed their skin abnormality to drugs. Cutaneous abnormalities observed by the dermatologist were also more common in patients with rheumatoid arthritis (76%) than in the group with non-inflammatory disease (60%). Specifically, bruising, athlete's foot, scars, rheumatoid nodules and vasculitic lesions were more common in patients with rheumatoid arthritis than in controls. The presence of bruising was predicted only by current steroid use. The presence of any other specific cutaneous abnormalities was not predicted by any of the variables assessed. In the whole group, current steroid use and having rheumatoid arthritis were the only important predictors of having any cutaneous abnormality. Conclusions: Self-reported and observed cutaneous abnormalities are more common in patients with rheumatoid arthritis than in controls with non-inflammatory disease. These include cutaneous abnormalities related to side effects of drugs or to rheumatoid arthritis itself and other abnormalities previously believed to be independent but which may be of clinical importance.